Quantification of the directional detection capability of the DRIFT-IIe dark matter search detector via the range of nuclear recoil tracks in two dimensions - Schuckman, Frederick G., II, author; Harton, John, advisor; Toki, Walter, committee member; Mooney, Michael, committee member; Marconi, Mario, committee member (Colorado State University. Libraries, 2021)
Evidence suggests that 83% of the matter content of the universe is dark matter. Despite its ubiquity, the identity of this matter is unknown. It is thought that a halo of dark matter surrounds and is distributed throughout our galaxy. The Weakly Interacting Massive Particle (WIMP) has been a popular dark matter candidate. As we move through this halo it should appear as a wind of WIMPs incident upon us. A properly-placed detector could have this wind blow through its top face at one time in the day, and through a side face 12 sidereal hours later. DRIFT-IIe is a low-pressure gas negative-ion time projection chamber designed for direct and directional detection of WIMPs elastically scattering from gas nuclei. Partial directional information of a WIMP recoil could be extracted by measuring the range of the track of ionization that it produces in two dimensions. To study this signature, the detector was exposed to a source of neutrons in a series of runs. In one run the source was placed above the detector and in a second run the source was placed to the side of the detector. Neutron recoils mimic those expected from WIMPs, and the source placement mimics a specific WIMP wind direction. For the two runs, the range information was compared with a Monte Carlo resampling test. It was found on average 302 +/- 4 neutron recoils, sampled with WIMP-like energy spectra, are required along each of these axes to discern the two populations with a significance of 3σ.
Keywords: directional; dark matter; nuclear recoil